Kewenangan Pemerintah Daerah dalam Mengendalikan Pembangunan Kawasan Bandar Udara - Ni Wayan Lusiana Sari; Desak Gde Dwi Arini; Luh Putu Suryani (Jurnal Preferensi Hukum, 2020)
Aviation safety and security is our shared responsibility. Accidents and incidents caused by kite games or other similar games can result in casualties, machine damage and weaken the level of compliance. I Gusti Ngurah Rai Airport Flight Operational Safety Area is air, land and water space with a radius of 15 km from the runway at I Gusti Ngurah Rai Airport. The plane that was flown by SYD - DPS was not allowed to land because of a kite near the end of Runway 27 so that my plane had to spin around. The research objective is to study and analyze regional arrangements and the authority of local governments in controlling the development of the airport area. This research uses a normative type of research, by examining library materials by studying and examining theories of concepts, as well as regulations relating to problems. The results showed that the Airport Flight Operations Safety Zone Arrangement was stipulated based on the Government Regulation on aviation security and safety, which stipulates that airport operators are obliged to protect the airport environment in order to avoid disturbances that slow down flights. The authority of a regional government in controlling the flight area is to organize spatial planning in its area while still understanding the rights that people have in accordance with applicable regulations.